PHYSIOLOGICAL CHARACTERISTICS OF INDONESIAN PARA-BADMINTON ELITE ATHLETES CLASS SL-3 & SL-4 - Indra Awaludin, Iqbal
Background: Badminton is one of the most popular sports in the world that can be played by all levels of society, including those with disabilities. At the 2022 Tokyo Paralympics, the Indonesian contingent managed to become the overall champion in the Para-Badminton number. This study used the Cosmed Wearable Metabolic System K5 tool which aims to assess the physiological characteristics of Indonesian elite Para-Badminton athletes during match simulations. The results of these data can be used as a reference in planning the right training design method according to the required training program. Methods: This research is an observational study. Overall, 5 Indonesian elite Para-Badminton athletes (SL3 and SL4) are currently focusing their training on preparing for the Asia-ParaGames in HangZhou, China. 5 athletes were recruited to be the subjects. All participants completed 3 testing sessions. The first session to measure anthropometry. The second session measured the athlete's VO2max level with the Balke protocol test, and the third session the athlete performed a match simulation using the Cosmed K5 portable metabolic device and measured blood lactate levels. Results: a total of 5 athletes were analyzed. The variable results of VO2 while using Cosmed K5 show that SL3 has a higher value compared to SL 4. Furthermore, lob movement techniques are more often used by Para-Badminton athletes number SL-3 Indonesia. Then lobs and drive shots are often used for SL-4 numbers. Comparison of blood lactate between sets 1&2 and sets 3&4 did not show a significant difference in SL-3 (p=0.26 in sets 1&2, and p=0.79 in sets 2&3), nor did SL4 (p=0.12 in sets 1&2). sets 1&2, and p=0.84 in sets 2&3). Conclusion: Para Badminton has a lot in common with badminton in general such as a wide field, playing rules and game numbers. It is important to develop special training programs for athletes with disabilities to suit their type and level of disability. Para Badminton can be a means of work for the troubled community so that they can contribute to the name of the nation.